Dietary Diversity Is Associated With Memory Status in Chinese Adults: A Prospective Study - Zhang, Jian; Zhao, Ai; Wu, Wei; Yang, Chenlu; Ren, Zhongxia; Wang, Meichen; Wang, Peiyu; Zhang, Yumei (Frontiers in Aging Neuroscience, 2020)
Background and aim: Subjective memory complaints are common in elderly people. Nutrition plays an important role in keeping brain health, however, the evidence on dietary diversity and subjective memory status is limited. This study aimed to investigate the effect of dietary diversity score (DDS) on memory status in Chinese adults in a prospective cohort study. Methods: Data of the China Health and Nutrition Survey was used in this study. A total of 4356 participants aged 50 years or older were enrolled in the analysis. DDS was calculated based on the dietary recall data collected in the wave of 2011. Information on self-report memory status (OK, good, or bad) and memory change in the past 12 months (stayed the same, improved, or deteriorated) were obtained from the wave of 2015. A memory score was calculated based on a subset of items of the Telephone Interview for Cognitive Status-modified. Multinomial logistic regression models were used to estimate the associations of DDS with memory status and memory change, and linear regression models were carried out to estimate the association between DDS and memory score. Results: In the study population, the percentages of participants who thought their memory was OK, bad, and good were 43.3%, 24.3%, and 32.4%, respectively. There were 1.4% of participants reported memory improvement in the past 12 months and 47.2% reported memory decline. Average memory score among participants was 12.8±6.1. Compared with participants who thought their memory was OK, a higher DDS was associated with self-reported good memory (Odds Ratio [OR] 1.15, 95%CI 1.07-1.24) and inversely associated with bad memory (OR 0.82, 95%CI 0.75-0.89). In subgroup analysis, however, in participants aged 65 years and above, the association between DDS and self-reported good memory was insignificant (OR 1.09, 95%CI 0.94-1.25). Compared with participants whose memory stayed the same, higher DDS was inversely associated with memory decline (OR 0.85, 95%CI 0.80-0.91). Besides, higher DDS was associated with higher memory score (beta 0.74, 95%CI 0.56-0.91). Conclusion: This study revealed that higher DDS was associated with better memory status and was inversely associated with self-reported memory decline in Chinese adults.